New Energy Sources, Technologies, and Systems: The Priority of Social, Climate, and Environmental Issues - Jurgen-Friedrich Hake; Liliana Proskuryakova (Foresight and STI Governance, 2018)
The introductory article to the special issue “The Future of Energy” is devoted to promising areas of development of the global energy complex, the assessment of their contribution to overcoming global challenges, and ensuring sustainable development. The trends under consideration differ significantly in the rate of evolution. Prospective development trajectories present both opportunities and risks specific to the fuel and energy complex of a particular country. Success in using emerging advantages and leveling threats depends upon a combination of internal and external factors, including the choice of public policy measures and the effectiveness of their implementation.